IMPLEMENTASI AUGMENTED REALITY DALAM MEMPROMOSIKAN PERUMAHAN PADA CV. PENTALAND JAYA ABADI - Abdul Aziz Khusen; Triase Triase; Raissa Amanda Putri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Promotion is an activity carried out to convey, disseminate, and offer products, so that potential consumers are interested in buying. In the implementation of the promotion, CV. Pentaland Jaya abadi uses website media and brochures that still contain 2-dimensional images and information about housing so that potential consumers are less interested because consumers cannot see the exterior and interior shapes directly. Potential consumers usually get brochures through project locations that are still under construction, after that contact the marketing department. One way to solve this problem can be to use augmented reality technology with the appropriate development method is the Multimedia Development Life Cycle (MDLC) which includes Concept, Design, Material Collecting, Assembly, Testing, and Distribution so that this research can produce an android-based augmented reality application that can display 3 dimensional virtual shapes from 3 housing estates including calista haus, grand ayahanda residence and calista homey. From each housing produces 3 dimensional objects on the exterior and interior so that it can provide interest in buying house objects and in addition to that it also helps in the marketing department in promoting housing objects without the need to show many miniatures that require time and also large places. Keywords: Promotion, Brochure, Multimedia Development Life Cycle, Augmented                 Reality Abstrak: Promosi merupakan suatu kegiatan yang dilakukan untuk menyampaikan, menyebarkan, dan menawarkan produk, supaya calon konsumen tertarik untuk membeli. Dalam pelaksanaann promosi CV. Pentaland Jaya Abadi menggunakan media website dan brosur yang masih yang berisi gambar 2 dimensi dan informasi tentang perumahan sehingga calon konsumen kurang tertarik disebabkan konsumen tidak bisa melihat bentuk eksterior dan interior secara langsung. Calon konsumen biasanya mendapatkan brosur melalui lokasi proyek yang masih dalam proses pembangunan, setelah itu menghubungi kebagian marketing. Salah satu cara mengatasi masalah ini dapat menggunakan teknologi Augmented Reality dengan metode pengembangan yang sesuai adalah Multimedia Development Life Cycle (MDLC) yang meliputi Concept, Design, Material Collecting, Assembly, Testing, dan Distribution sehingga penelitian ini dapat menghasilkan aplikasi Augmented Reality berbasis android yang dapat menampilkan bentuk virtual 3 dimensi dari 3 perumahan diantaranya Calista Haus, Grand Ayahanda Residence dan Tuasan Homey. Dari masing-masing perumahan menghasilkan objek 3 dimensi pada bagian eksterior dan interior sehingga dapat memberikan ketertarikan untuk membeli objek rumah dan selain itu juga membantu pada bagian marketing dalam mempromosikan objek perumahan tanpa perlu memperlihatkan banyak miniatur yang membutuhkan waktu dan juga tempat yang besar. Kata kunci: Promosi, Brosur, Multimedia Development Life Cycle, Augmented Reality